FITNESS FOR SERVICE OF GAS COMPRESSOR PIPING USING FINITE ELEMENT METHOD - Ichsanudin, Muhammad; Prabowo, Imam; Istiqomah, Intan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This research presents a Level 3 Fitness for Service (FFS) analysis, focusing on stress evaluation in the suction side of gas compressor piping in a gas-fired power plant in Indonesia, using the Finite Element Method (FEM). To expedite numerical calculations and reduce computational time, the analysis employs line elements within FEM, enabling efficient and timely assessment. The modeled operational conditions include sustained, expansion, and occasional seismic loads, providing a comprehensive view of pipeline behavior under various stress scenarios. The study results indicate that all pipeline segments analyzed show no potential for failure, with code ratios below 1. The sustained load has a code ratio of 0.71 with a maximum stress of 97.64 MPa, an expansion load of 0.66 with a maximum stress of 136.90 MPa, and an occasional seismic load, the highest at 0.70 with a maximum stress of 129.27 MPa. Among all loading scenarios, the compressor suction segment exhibits the highest code ratio, indicating the need for heightened attention in maintenance management. It is recommended that condition monitoring and inspection efforts be focused on this segment to prevent potential failure. The findings conclude that all code ratios from each loading scenario are acceptable, confirming that the pipeline segments meet the required safety standards. This reinforces the reliability of the pipeline system and validates the effectiveness of Level 3 FFS analysis in guiding maintenance strategies and risk management for critical gas pipeline systems.